Spatial distribution features and geological settings of the largest gold deposits - E. M. Necrasov; L. A. Dorojkina (Известия высших учебных заведений: Геология и разведка, 2015)
The paper considers the problem of distribution and tectonic setting of the largest gold deposits in folded and folded-blocked belts of different types and ages. We present a generalized scheme showing a distribution of 14 giant deposits (with the amount of mined metal, remaining gold reserves and economical gold resources of more than 1000 tons) as well as other deposits with reserves being smaller in mineralization but close to the giant ones. Spatial distribution of deposits in relation to regional faults, accompanying faults, high-orders (3-5'th) faults has been shown, as well as ore-bearing environment that is most favorable for the localization of the largest accumulations of ore and gold reserves.